2015
DOI: 10.3390/molecules200813563
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Cytotoxic Compounds from Aeschynomene fascicularis, a Mayan Medicinal Plant

Abstract: Abstract:The plant Aeschynomene fascicularis (Fabaceae) has been used in Mayan traditional medicine in the Yucatan peninsula. However, the compounds present in the plant responsible for its curative properties have not yet been investigated. Aeschynomene fascicularis root bark was extracted with 100% methanol to obtain a crude extract. The methanol extract was partitioned successively with solvents with increasing polarity to obtain the corresponding hexane (Hx), dichloromethane (DCM) and ethyl acetate fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
1
11
0
1
Order By: Relevance
“…It is native to the tropical Africa and Madagascar, cultivated in Egypt, Java and South America [12], Plants of genus Aeschynomene are reported to exert hepatoprotective [13], antimicrobial [14], cytotoxic [15], antioxidant [16], anthelmintic [17] and anti-inflammatory activities [18]. Preliminary phytochemical studies among different Aeschynomene species revealed the presence of flavonoid glycosides [19], pterocarpans [20] and chalcones [21]. On other hand, only some kaempferol derivatives were isolated from A .…”
Section: Introductionmentioning
confidence: 99%
“…It is native to the tropical Africa and Madagascar, cultivated in Egypt, Java and South America [12], Plants of genus Aeschynomene are reported to exert hepatoprotective [13], antimicrobial [14], cytotoxic [15], antioxidant [16], anthelmintic [17] and anti-inflammatory activities [18]. Preliminary phytochemical studies among different Aeschynomene species revealed the presence of flavonoid glycosides [19], pterocarpans [20] and chalcones [21]. On other hand, only some kaempferol derivatives were isolated from A .…”
Section: Introductionmentioning
confidence: 99%
“…R. communis seeds, leaves, fruit, stem and bark are used in different traditional therapeutic practices by local practitioner (Hakeem) [ 21 ]. Therefore, the toxicity profiling (using bioassays) of such important plants is very helpful to appraise the safety [ 22 33 ]. In this regard, the bioassays (hemolytic and brine shrimp) are the standard tests to evaluate the cytotoxicity, whereas TA98 and TA100 (based on salmonella mutant strains) are the reference tests for mutagenicity evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of growth inhibition was determined using a MTT colorimetric technique to measure four viable cells (HL-60 human myeloid leukemia, SMMC-7721 hepatocellular carcinoma, A-549 lung cancer and MCF-7 breast cancer) with minor modification [18,19]. A total of 5000-10,000 exponential phase cells per well were seeded onto a 96-well plate for 24 h, Each tumor cell line was exposed to a test compound at concentrations of 0.0624, 0.32, 1.6, 8, and 40 µM in DMSO in triplicate for 72 h, with cisplatin as the positive control.…”
Section: Anti-proliferative Activitymentioning
confidence: 99%